Lok adalats in India - Deshta, Sunil (New Delhi, 1995)
This book dealt with a very important and stimulating theme of contemporary relevance. Lok Adalats as an alternative mode of dispute settlement has come to be accepted as a viable, economic efficient and informal one.
Keywords: Lok adalats-India